Geomorfología como herramienta de zonificación: Caso Chalaypampa, Angares – Huancavelica - León Ruiz, Christian (2022)
The investigation corresponds to the geological, geomorphological and geodynamic analysis of the Chalaypampa sector as a new urban area for the relocation of the political center of the Chincho district, in the Angares province, in the Huancavelica department, for presenting imminent danger to the physical and psychological integrity of the families that they live in the current urban area of said district considered high risk as a consequence of an identified geological fault and its relationship with intense rains in the area. The methodology developed is descriptive correlational, based on observation, which allows specifying and describing the characteristics and phenomena under geological contexts that occur in the research environment while evaluating the variables that condition each physical space over time. The district of Chincho was classified as high risk, by the Regional Government of Huancavelica, and verified by the Geological, Mining and Metallurgical Institute (INGEMMET), so it is of the utmost importance for the urban area of the district a prompt reassignment in a sector that has the appropriate geological and geomorphological conditions for urban planning. This evaluation concludes that the Chalaypampa sector presents the necessary conditions for resettlement considering certain limitations that are presented in this investigation.